Analysis of Regional Financial Management Performance Based on the Value for Money Perspective - Kasmawati Kasmawati; Sadly Abdul Djabar; Syamsuddin Bidol (Scieclouds Publishing, 2026)
Value for Money is a management concept in the public sector based on three key elements: economy, efficiency, and effectiveness. Value for Money is crucial in public sector organizations because it embodies the principle of getting the most value for money. The objective of this study is to analyze the performance of local government financial management from a value-for-money perspective, which encompasses economic aspects, efficiency, and effectiveness. This study was conducted at the Regional Finance and Asset Agency of South Sulawesi Province. This study employs a mixed-methods approach using both primary and secondary data sources. The quantitative analysis involves examining budget data and actual local government expenditures for the 2021–2024 period, while the qualitative analysis consists of interviews, observations, and document review to support the findings of the quantitative analysis. Research method: explanatory sequential design. Based on the results of a study on the measurement of the financial performance of the Regional Finance and Asset Agency using the concept of value for money, it was found that: (1) The financial performance of the South Sulawesi Provincial Regional Finance and Asset Agency is classified as economical. This is indicated by an economic ratio that has consistently remained below 100% each year; (2) Financial performance is classified as efficient, as the efficiency ratio indicates that regional expenditures are relatively smaller than the revenue generated; (3) Financial performance is classified as fairly effective, as the effectiveness ratio is below 100%, indicating that revenue realization has not yet fully met the set targets; (4) Overall, the financial performance of the South Sulawesi Provincial BKAD reflects the application of the value-for-money principle, particularly in terms of economy and efficiency, while effectiveness still needs to be improved to ensure more optimal achievement of revenue targets in the future.